Shared housing, shared lives - Heath, Sue, 1964- author.
1 online resource (xix, 238 pages)
Keywords: With a growing population, rising housing costs and housing providers struggling to meet demand for affordable accommodation, more and more people in the UK find themselves sharing their living spaces with people from outside of their families at some point in their lives. Focusing on sharers in a wide variety of contexts and at all stages of the life course, Shared Housing, Shared Lives demonstrates how personal relationships are the key to whether shared living arrangements falter or flourish. Indeed, this book demonstrates how issues such as finances, domestic space and daily routines are all factors which can impact upon personal relationships and wider understandings of the home and privacy. By directing attention towards people and relationships rather than bricks and mortar, Shared Housing, Shared Lives is essential reading for students and researchers in fields such as sociology, housing studies, social policy, cultural anthropology and demography, as well as for researchers and practitioners working in these areas